Deuterium irradiation resistance and relevant mechanism in W–ZrC/Sc2O3 composites prepared by spark plasma sintering. (February 2020) - Yao, Gang; Chen, Hong-Yu; Fu, Ming-Qi; Luo, Lai-Ma; Zan, Xiang; Xu, Qiu; Tokunaga, Kazutoshi; Zhu, Xiao-Yong; Wu, Yu-Cheng
Abstract: To study the D2 retention behavior of W–ZrC/Sc2 O3 composites, mirror-polished samples prepared by spark plasma sintering (SPS) were exposed to different irradiation doses at room temperature (RT). TDS measurements were subsequently performed from RT to 900 K. Results revealed that Sc2 O3 particles did not benefit the D2 + ion irradiation resistance, whereas W–1vol% ZrC/2 vol% Sc2 O3 composites showed superior irradiation resistance over other samples. D2 implantation was also performed at 523 K with the irradiation dose of 1 × 10 20 D2 + /m 2 to study the influence of temperature on D2 retention during the capture process, which could apparently decrease D2 retention by low-energy traps. Only small dislocation loops or precipitates were observed in W–1vol% ZrC/2 vol% Sc2 O3 sample after irradiation up to 1.0✕10 21 D2 + /m 2 . Highlights: The effect of ZrC/Sc2 O3 doping on irradiation resistance behavior of W materials was investigated. 1 vol% ZrC/2 vol% Sc2 O3 composite possess better irradiation resistance than SPS/W. Increasing implantation temperature decrease D2 retention by low-energy traps.